2020
DOI: 10.1088/1741-2552/ab5ee9
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation-induced SSSEP as an objective index to evaluate the difference of tactile acuity between the left and right hand

Abstract: Objective. The objective of this study is to propose an objective index to evaluate the difference of tactile acuity between the left and right hand based on steady-state somatosensory evoked potential (SSSEP). Approach. Two kinds of tactile sensations (vibration and pressure) with three levels of intensities (low/medium/high) were evoked on two finger areas of the left or right hand (thumb and index for healthy hands, thumb and index-projected areas for disabled hands) via transcutaneous electrical nerve stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…There are currently two reports using SSEPs to study ETS. Wang et al ( 2021 ) used EEG to analyze a subject with amputation and showed the EEG characteristics of different stimulation sites; Su et al ( 2020 ) initially studied the amplitude of SSEPs as an evaluation indicator of feeling. Unlike previous studies, the Oddball paradigm used in this article is to investigate the main cognitive component P300 (Kanda et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are currently two reports using SSEPs to study ETS. Wang et al ( 2021 ) used EEG to analyze a subject with amputation and showed the EEG characteristics of different stimulation sites; Su et al ( 2020 ) initially studied the amplitude of SSEPs as an evaluation indicator of feeling. Unlike previous studies, the Oddball paradigm used in this article is to investigate the main cognitive component P300 (Kanda et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Breitwieser et al (2012) further applied SSSEP to five fingers of the right hand and proved that it can classify different fingers with SSSEP. Su et al (2020) explored the relation between stimulation intensities and SSSEP. Their results revealed that SSSEP amplitude is positively correlated with the intensity of stimulation and could be used as an index to evaluate the tactile acuity.…”
Section: Sensory-and Motor-related Paradigmsmentioning
confidence: 99%
“…The value of measured pinch distance was used to modulate the stimulation frequency, meanwhile pulse width and current amplitude were fixed as 200 µs and 3 mA, respectively. These two parameters have been used in our previous work [31,32]. Eight subjects in the previous study were recruited again in this study.…”
Section: Prosthetic Finger Position Controlmentioning
confidence: 99%
“…Frequency modulation resulted in changes of the perceived sensation density. It has been demonstrated that subjects were more sensitive to the change of stimulated frequencies when compared to pulse widths [32]. Here, the frequency modulation was used for stimulation encoding to get a more effective discrimination for the applied stimulation and a better matching between the perceived sensation and feedback information.…”
Section: Prosthetic Finger Position Controlmentioning
confidence: 99%